I’jaz Al-Qur’an Menurut Pandangan Orientalis J. Boullata - Lukman Fajariyah Addim (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
The Quran is a Muslim holy book that was revealed through the Prophet Muhammad. Al-Quran as the greatest revelation at the same time serves as a guide to life that must be believed and guided. Besides, it should also be noted that the Qur'an which contains Islamic treatises also implies amazing lessons called miracles. This paper aims to explore aspects of i'jaz Al-Quran from a non-Muslim perspective, namely Issa J. Boullata. The research method used in this study is a qualitative-descriptive method with a content analysis approach, where the author seeks to describe and analyze Boullata's reviews and perspectives on i'jaz Al-Quran. The findings of this study are; first, the linguistic aspects of the Qur'an are challenges (tahaddi) that cannot be matched even by Arabic experts. Second, the size of the miracles of the Koran includes the entire letter in it and not partial. Third, a series of letters arranged neatly into the object of i`jaz Al-Quran. Also, note that i'jaz Al-Quran is proof of Muhammad's prophethood.